Record of Phtheochroa fulvicinctana (Constant, 1893), Cydia vallesìaca (Sauter, 1968) and Dichrorampha consortana (Stephens, 1852) new far the ltalian fauna ( Lepidoptera Tortricidae ) (Bollettino di zoologia agraria e bachicoltura, 2024)
Remarks about Phtheochroa fulvicinctana (Constant, 1893), Cydia vallesiaca(Sauter, 1968) and Dichrorampha consortana (Stephens, 1852) collected in Italyare reported. Ph. fulvicinctana and C. vallesiaca are new for the ltalian fauna, thepresence of D. consortana in Italy is confirmed.
Keywords: Lepidoptera Tortricidae; new records; ltaly